2010
DOI: 10.1590/s0066-782x2010000300020
|View full text |Cite
|
Sign up to set email alerts
|

Resultados imediatos e tardios da valvoplastia mitral percutânea em pacientes com estenose mitral

Abstract: Background: The analysis of immediate and long-term results of mitral valvoplasty by balloon catheter (MVRBC) are still lacking in literature, mainly in the national context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(65 reference statements)
0
4
0
1
Order By: Relevance
“…The success of balloon mitral valvotomy is characterised by an increased valvular area > 25% of the initial area and a mitral valvular area ≥ 1.5 cm 2 in the absence of mitral regurgitation > 2+, according to angiographic criteria. 9,10 The patient had an echocardiographic score of 10, subvalvular stenosis (3), thickening (2), mobility (3), and calcification (2). On radioscopy, she had a calcification of 2++.…”
Section: Discussionmentioning
confidence: 99%
“…The success of balloon mitral valvotomy is characterised by an increased valvular area > 25% of the initial area and a mitral valvular area ≥ 1.5 cm 2 in the absence of mitral regurgitation > 2+, according to angiographic criteria. 9,10 The patient had an echocardiographic score of 10, subvalvular stenosis (3), thickening (2), mobility (3), and calcification (2). On radioscopy, she had a calcification of 2++.…”
Section: Discussionmentioning
confidence: 99%
“…8 Destaque especial quanto ao risco de reestenose foi dado, em recente análise de Cardoso et al 9 , à área valvar mitral pré-procedimento e à presença de calcificação mitral acentuada. O sucesso parcial do procedimento, ou resultado subótimo (obtenção de área valvar < 1,5 cm² na ausência de insuficiência mitral grave), também é um preditor de reestenose mitral precoce.…”
Section: Discussionunclassified
“…Mitral Valve Disease • Regarding percutaneous commissurotomy, studies in Brazil have shown a much higher proportion of females (85%)coincident with the epidemiology of RHD and noticeably mitral stenosis -and of young people (<40 years). 221,222 Aortic Valve Disease…”
Section: Complications and Associated Diseasesmentioning
confidence: 99%